Zebrafish Clock rhythmic expression reveals independent peripheral circadian oscillators - Whitmore, David; Foulkes, Nicholas S.; Strähle, Uwe; Sassone-Corsi, Paolo (Nature neuroscience, 1998)
The only vertebrate clock gene identified by mutagenesis is mouse Clock, which encodes a bHLH-PAS transcription factor. We have cloned Clock in zebrafish and show that, in contrast to its mouse homologue, it is expressed with a pronounced circadian rhythm in the brain and in two defined pacemaker structures, the eye and the pineal gland. Clock oscillation was also found in other tissues, including kidney and heart. In these tissues, expression of Clock continues to oscillate in vitro. This demonstrates that self-sustaining circadian oscillators exist in several vertebrate organs, as was previously reported for invertebrates.